The Effect of Size Factors on the Mechanical Strength of Meranti Wood - Agung Nugrawan Kutana; Irma Wahyuningtyas; Heriad Daud Salusu (Andalasian International Journal of Applied Science, Engineering and Technology, 2026)
The use of wood as a construction material has been increasing in recent years. However, wood has limitations in terms of availability and size, which can affect the strength capacity of structural materials. Therefore, the efficient use of raw materials must be carefully considered in structural and construction planning. One important parameter related to this efficiency is the size factor of wood samples. The objective of this study was to analyze the effect of different sizes of meranti wood (Shorea spp.) used as structural elements on its mechanical properties, such as flexural properties (stiffness and strength) and compressive strength parallel to the grain. The results showed that both empirical observations and theoretical standards indicate a decrease in MOE values as the size of the test samples increases. Larger samples tend to produce lower MOR, bending strength, and compressive strength values. These findings indicate that the size factor plays an important role in determining the mechanical performance of wood and should be considered in structural design using wood materials.